Leadership Development in Ophthalmology: Current Impact and Future Needs - Berkowitz, Sean T.; Law, Janice C.; Sternberg, Paul, Jr.; Patel, Shriji (Journal of Academic Ophthalmology, 2021)
Importance There is a lack of peer-reviewed literature on leadership development programs (LDP) in ophthalmology. Research into LDP demographics, outcomes, and methodology is needed.Objective The aim of the study is to evaluate the extent to which LDPs targeting ophthalmologists meet the needs of emerging leaders.Design The design type of the study is cross-sectional analysis.Setting This study involves international setting.Participants The participants involved were ophthalmologists at any career level.Methods Routine internet search was used to identify LDPs targeting ophthalmologists. LDPs identified were categorized by the outcome data available into four levels based on prior literature. Participants were assessed using previously validated software for gender (Gender-API, 2020) and race or ethnicity (NamSor, 2020)Results Nine programs were identified which were classified into LDP generations. The first LDP in ophthalmology was the American Academy of Ophthalmology (AAO) LDP, which served as the nidus for the formation of four multinational LDPs, together forming the Global LDP. These LDPs were similar in size and scope; program size ranging from nine to 30 participants; a length of 1 to 2 years; with similar curricular offerings; with funding primarily derived from cost-sharing with a nominating society. The second generation of ophthalmology LDPs in the United States has targeted female scientists or faculty (Women's LDP by ARVO) and academic ophthalmology leaders (Academic LDP by Association of University Professors of Ophthalmology).The AAO's LDP appears increasingly diverse with approximately 13% women at inception, gradually increasing from 40 to 65% women in the last 5 years (n = 389). There has also been a notable increase in ethnic diversity.Conclusion and Relevance AAO LDP is the preeminent leadership training program for ophthalmologists, and it has influenced the creation of a new generation of LDP offerings. There remains a paucity of LDP evaluation metrics and reported outcomes. Newer iterations are successfully targeting academic leadership and attempting to address known disparities in gender and race or ethnicity. Further expansion of LDPs and related research can ensure equity and diversity in the pipeline.
Keywords: leadership development program; ophthalmology; leadership